Do the type of walking surface and the horse speed during hippotherapy modify the dynamics of sitting postural control in children with cerebral palsy?. (December 2019) - Flores, Fabiana Moraes; Dagnese, Frederico; Copetti, Fernando
Abstract: Background: Hippotherapy is described as a rehabilitation method for postural control in children with cerebral palsy. Horse's movements can be manipulated during hippotherapy's sessions with horse walking on different surfaces and at different speeds. The purpose of this study was to assess if dynamic sitting postural control in children with cerebral palsy in hippotherapy is modified when surfaces (sand or asphalt) and horse's walking speed (slow or faster) are changed. Methods: Sixteen children participated in this crossover study. Eight bilateral spastic cerebral palsy children, age range (6–12 years), with Gross Motor Function Classification System levels III to IV, practicing hippotherapy and eight children with typical development (reference group), matched for age and sex. All children were evaluated during riding a horse on sand and asphalt surfaces and at slow (self-selected) and faster (30%) horse's walking speed. Center of pressure parameters were determined by a portable pressure measurement system positioned on the saddle. Findings: Mediolateral displacement amplitude of the center of pressure was larger when the horse was on sand. Mediolateral and anteroposterior displacements amplitude and velocities of the center of pressure increased at horse's faster walking speed. Interpretation: Our study test empirical procedures used in clinical practice and with a population widely reached by hippotherapy. In order to increase the demand for sitting postural control in children with cerebral palsy during horse riding, faster horse speed or riding on sand should be used. Highlights: Horse's movements can be manipulated in hippotherapy sessions. Manipulations enhance demand for postural control in children with cerebral palsy. Increases in horse's walk speed changes center of pressure parameters. Different types of walking surfaces do not change all center of pressure parameters.